Developing a high-fidelity simulated-learning environment (SLE) in audiology education: A preliminary investigation - Mohd Puzi, Nur Ain Fathanah; Dzulkarnain, Ahmad Aidil Arafat; Rahmat, Sarah; Badzis, Mastura; Che Azemin, Mohd Zulfaezal (2016)
Purpose: Challenges to improve the audiology training pedagogy have resulted in the increased demand in the use of a simulated learning environment (SLE). Numerous SLE tools were reported in the literature with the majority of the modules being low to medium fidelity. A high fidelity SLE training module could assist an instructor in providing a better exposure for the respective audiology students in both the basic and advanced clinical modules. Because of the paucity of SLE modules, a new training module is warranted. This study investigates the perceptions of audiologists in the use of high-fidelity SLE training modules and to get feedback regarding the common errors regularly made by students in routine audiology testing. Methods: Five audiology clinical preceptors were involved in this study (through face-to-face interviews) with years of experience ranging from 2 to 12 years. Results: Feedback from the audiologists was analysed based on thematic descriptive analysis. The general themes of the errors reported by the audiologists are classified based on, (i) knowledge-based errors, (ii) technical errors and, (iii) poor communication skills. Conclusion: Input gathered from this study was useful as basis for developing formative feedback modules in the development of a new high-fidelity SLE in audiology.